2017
DOI: 10.1371/journal.pntd.0006119
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the impact of low doses of nano-formulated benznidazole in acute experimental Chagas disease

Abstract: BackgroundChagas disease is a neglected parasitic infection caused by the protozoan Trypanosoma cruzi (T. cruzi) that affects more than 6 million people, mainly in Latin America. Benznidazole is still the drug of choice in many countries to treat it in spite of its dosage regimen and adverse side effects such as such as allergic dermatitis, peripheral neuropathy and anorexia. Thus, novel, safer, and more efficacious treatments for such neglected infection are urgently required.MethodologyIn this study, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 31 publications
4
52
0
Order By: Relevance
“…Within this framework, preclinical studies can shed some light on the use of variations in dosage, treatment schedules and interactions of known and unknown drugs. In this sense, we have studied experimental treatments with low doses of BNZ in acute (Grosso et al ., 2013; Scalise et al ., 2016; Rial et al ., 2017 a , 2017 b ) and chronic infection in mice (Rial et al ., 2016, 2017 a , 2017 b ), which is in line with pharmacokinetic studies in Chagas disease patients, supporting the hypothesis that treatment with lower BNZ doses may be effective (Fernández et al ., 2016; Wiens et al ., 2016), with an impact on the potential reduction of adverse effects (Bustamante et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Within this framework, preclinical studies can shed some light on the use of variations in dosage, treatment schedules and interactions of known and unknown drugs. In this sense, we have studied experimental treatments with low doses of BNZ in acute (Grosso et al ., 2013; Scalise et al ., 2016; Rial et al ., 2017 a , 2017 b ) and chronic infection in mice (Rial et al ., 2016, 2017 a , 2017 b ), which is in line with pharmacokinetic studies in Chagas disease patients, supporting the hypothesis that treatment with lower BNZ doses may be effective (Fernández et al ., 2016; Wiens et al ., 2016), with an impact on the potential reduction of adverse effects (Bustamante et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Rial et al . reported the formulation an in vivo evaluation of benznidazole nanocrystals for the treatment of Chagas disease [21]. Particularly, they observed a remarkable effect of low doses of nanoformulated benznidazole on immunosuppressed infected mice, indicating the potential importance of nanoformulated BNZ in experimental therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are not enough data to predict whether the nanoparticles will offer improved effective antichagasic treatments. Preclinical data analyzed herein has not yet clearly shown the successive elimination of intracellular parasites such as in chronic asymptomatic cases, or non-rodent immunized animal models 30,36,41,42,50,59,95,136,137. Moreover, the only nanoparticulate system approved for clinical trials is liposomal amphotericin B (LAMB), however, it has been shown to have little anti- T. cruzi activity 138,139…”
Section: Resultsmentioning
confidence: 96%
“…Rial et al42 evaluated C3H/HeN mice infected with T. cruzi in the acute phase using the Nicaragua (TcN) strain by administering benznidazole nanoparticles (BNZ-nps) orally with 10, 25 or 50 mg/kg/day. Mice treated with these nanoparticles survived until euthanasia (92 days after infection, dpi).…”
Section: General Aspectsmentioning
confidence: 99%